O sertão e o cativo : escravidão e pastoreio : os campos de Palmas - Paraná 1859-1888 - Machado, José Lucio da Silva (2014)
This work aims to observe the slave relations in areas facing the pastoral economy, highlighting the influence and contributions of enslaved workers in their development. Therefore, we sought to identify the theoretical models used by leading researchers who have written on this topic and justify our choice of the analysis model proposed by Jacob Gorender when addressing slavery in Brazil as a historically new mode of production. The paper discusses the different ways of tackling this issue, and ways of treatment when we refer to these workers. Through extensive literature review, the text seeks to demonstrate the initial process of colonization of Brazil, performing a historical survey about the introduction of the first cattle and slave laborers in Brazil. The text highlights the introduction of slave laborers from Africa and its distribution to different sectors of Brazil's economy, trying to point out the factors that favored such trafficking, also noting the changes on the native population. We analyze the development and expansion of pastoral activity, observing the regions where these activities predominated and the functions performed by enslaved workers in these areas. Finally, we address the Palmas fields observing the characteristics of the enslaved workers and occupations performed by the captives, establishing a relationship between their presence in these areas of creation, and their degree of involvement in field activities such as herding, but also in the work subsistence agricultural and domestic. We also point to the region of Palmas de Campos proportions between captive female and male, watching the occupations performed by these workers and the degree of dependence of the company in relation to the hand of enslaved work. We also analyze the movement of purchase and sale of such workers, their local circulation, the concessions of freedom and the conditions under which these relations have developed